Targeting of functional antibody-CD59 fusion proteins to a cell surface - Zhang, Hui-fen (American Society for Clinical Investigation, 1999)
Complement is involved in the pathogenesis of many diseases, and there is great interest in developing inhibitors of complement for therapeutic application. CD59 is a natural membrane-bound inhibitor of the cytolytic complement membrane attack complex (MAC). In this study, the preparation and characterization of antibody-CD59 (IgG-CD59) chimeric fusion proteins are described. Constructs were composed of soluble CD59 fused to an antibody-combining site at the end of C(H)1, after the hinge (H), and after C(H)3 Ig regions. The antigen specificity of each construct was for the hapten 5-dimethylamino-naphthalene-1-sulfonyl (dansyl). Correct folding of each IgG-CD59 fusion partner was indicated by recognition with anti-CD59 antibodies specific for conformational determinants and by IgG-CD59 binding to dansyl. The IgG-CD59 fusion proteins all bound specifically to dansyl-labeled Chinese hamster ovary cells and provided targeted cells, but not untargeted cells, with effective protection from complement-mediated lysis. Data indicate that CD59 must be positioned in close proximity to the site of MAC formation for effective function, and that modes of membrane attachment other than glycophosphatidylinositol linkage can affect CD59 functional activity.